Osteochondroma: A Literature Review with Case Illustrations - Firdaus, Nadine Aisyah Sultan; Aliyyu, Aisah; Zubaedi, Alisha Chaerani; Prawiro, Aurellia Wongso; Remtaya, Baiq; Rameci, Hadil Hudati Awwari; Aghni, Hasna Tazkia; Kusuma, I Gusti Ketut Artha Jaya; Ramadhan, Panji Sena; Mikailla, Romy Healthy (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Osteochondroma is the most common benign bone tumor, typically discovered during periods of skeletal growth. Although frequently asymptomatic, it may cause pain, deformity, neurovascular compression, or in rare instances undergo malignant transformation into secondary chondrosarcoma. This study presents a case-based literature review to illustrate the spectrum of clinical manifestations, diagnostic approaches, and management strategies of osteochondroma. Three representative cases were analyzed: a 52-year-old female with talar osteochondroma presenting with ankle pain and swelling; a 17-year-old male with distal femoral osteochondroma manifesting as a posterior thigh mass with minimal symptoms; and a 26-year-old female with Hereditary Multiple Exostoses (HME) who developed secondary chondrosarcoma. The comparison highlights that solitary lesions are often managed effectively with simple excision, while HME carries a higher risk of malignant transformation requiring more complex interventions, such as total hip replacement and adjuvant radiotherapy. Overall, osteochondroma generally has an excellent prognosis; however, careful evaluation and long-term monitoring are crucial, particularly in patients with HME.